ENVIRONMENTAL MANAGEMENT STRATEGY ON RIVERBANKS AS EROSION PREVENTION - Nurlita Pertiwi; Mithen Mithen; Nur Anny Suryaningsih Taufieq (International Conference on Social and Islamic Studies, 2021)
Riverbanks have important roles in maintaining river ecosystems. Erosion and sedimentation as the dynamics of watersheds determine the sustainability of river ecosystem functions. This study describes the determination of environmental management strategies on riverbanks to prevent erosion. The research method is descriptive quantitative. Three districts in South Sulawesi are the location of data retrieval as the managers of the Jeneberang River, Walanane River and Saddang River. The primary data sources were 27 experts consisting of 21 government officials and six experts from higher education. The data analysis method uses SWOT analysis which uses aspects of Strengths, Weaknesses, Opportunities and Threats. The results of data analysis indicate that the development of greenbelts on the riverbanks with local vegetation maintenance. Therefore, the strategy for achieving environmental quality on riverbanks is strengthening village institutions and education as an effort to increase community knowledge, attitudes and skills in local plant conservation on riverbanks.